Factors predicting mortality in a total population sample of the elderly. Issue 4 (December 1985) - Campbell, A J; Diep, C; Reinken, J; McCosh, L
Abstract : Between 1977 and 1979 an age stratified sample of people 65 years and over living in the community and in institutions in Gisborne, New Zealand was assessed medically and socially. This sample was followed and reviewed in 1982. At follow up 308 subjects were seen, 227 had died, and 24 had left the area. Factors predicting mortality were assessed. Using a log rank test, factors predicting mortality included age, impaired mental function, functional disability, urinary incontinence, prescribed drugs, pulse pressure, erythrocyte sedimentation rate (ESR), systolic pressure, cardiovascular drugs, and falls. However, a number of these factors increased in prevalence with age. Using a Cox's regression analysis for factors predicting mortality after controlling for age, the following were found to be significant predictors: impaired mental function; functional disability; urinary incontinence; prescribed drugs, ESR and falls. A proportional hazards general linear model showed that the major predictors of mortality in old age were markers of established disease.